2017
DOI: 10.1186/s40463-017-0231-1
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopically-assisted transmastoid approach to the geniculate ganglion and labyrinthine facial nerve

Abstract: BackgroundEndoscopic transcanal approaches to the facial nerve allow excellent exposure of the tympanic facial nerve. This approach becomes limited when access is required to the more proximal geniculate ganglion and labyrinthine portion of the facial nerve. The aim of this report was to determine the feasibility of a transmastoid endoscopically assisted approach to the geniculate ganglion and labyrinthine facial nerve. This is an endoscopic cadaveric dissection and video review at a university anatomical labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 16 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…Recently some authors described the radiologic criteria (petrous bone CT scan) which permit preoperatively to predict the feasibility of this type of approaches 7 . Other authors suggested to improve the limited visualization of the trans-mastoid approach with endoscopic assistance in a cadaveric study 18 . To gain adequate surgical exposure through this approach several reports suggest to uncover the middle cranial fossa dura through the TMA, to permit temporal lobe retraction, gaining a better exposure of the geniculate ganglion area [8][9][10] .…”
Section: Discussionmentioning
confidence: 99%
“…Recently some authors described the radiologic criteria (petrous bone CT scan) which permit preoperatively to predict the feasibility of this type of approaches 7 . Other authors suggested to improve the limited visualization of the trans-mastoid approach with endoscopic assistance in a cadaveric study 18 . To gain adequate surgical exposure through this approach several reports suggest to uncover the middle cranial fossa dura through the TMA, to permit temporal lobe retraction, gaining a better exposure of the geniculate ganglion area [8][9][10] .…”
Section: Discussionmentioning
confidence: 99%
“…7 Another study mentioned the role of endoscope-assisted transmastoid approach facial nerve decompression involving the second genu and the labyrinthine segment of the facial nerve. 8 With regard to our case, the conventional transmastoid approach was initially performed. However, the lesion at the distal portion of the tympanic segment of the facial nerve was obstructed by the dome of the lateral semicircular canal with the surgical microscope.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have promoted the transcanal endoscopic "inside-out" technique, 10-14 endoscopic assisted intramastoid dissection, 15 and robotic-guided approaches. [16][17][18] However, no study has yet focused on a minimally invasive burr hole endoscopic approach through a small postauricular incision.…”
Section: Introductionmentioning
confidence: 99%